Does Financial Vulnerability linked between Innovation and Firm Performance? (KASBIT Business Journal, 2025)
Generally, Innovation is strategic tool is used for development of firms and enhance the firm performance (FP) and lowers the financial vulnerability (FV) of firms. The aim of this study is to check the impact of innovation on FP as well as on FV and check the mediating role of FV between innovation and FP in non-financial firms listed at Pakistan Stock Exchange (PSX) from study period of 2016 to 2023. Innovation is measured through product innovation (PI) and market innovation (MI). FV is measured through four proxy’s equity ratio (ER), revenue concentration ratio (RCR), administrative cost ratio (ACR) and operating margins (OM). FP is measured through return on assets (ROA) and return on equity (ROE). To add more strength in model control variables firm size (FS) and leverage (Lev) is used in this study. Data is collected manually from annual reports of 138 firms out of 418 and regression test employed. Findings shows that innovation has positive significant effects on FP and also innovation decreases the FV of firms. FV mediate this relationship between innovation and FP. Findings are consistent with expectations. This study has contribution in literature and has implications for managers, investors and stakeholders of firms. Policy makers and mangers should focus on innovation to lower the financial shocks and enhances FP.
Keywords: Innovation, Financial Vulnerability, Firm Performance, Non-Financial sector, Pakistan.